High anaemia and iron deficiency prevalence among pregnant women living in low groundwater iron areas of Bangladesh - Mohammed Imrul Hasan; Shamim Ahmed; Alistair R. D. McLean; A. M Quaiyum Rahman; Mohammad Saiful Alam Bhuiyan; S. M. Mulk Uddin Tipu; Sabine Braat; Shams El Arifeen; Jena D. Hamadani; Sant-Rayn Pasricha; Eliza M. Davidson (BMC Public Health)
Abstract Background Anaemia is a significant public health concern in Bangladesh, yet data on the prevalence of anaemia in pregnancy and the contribution of iron deficiency are limited. Given the reliance on groundwater for drinking, a better understanding of the role of drinking water iron in anaemia aetiology is also required to inform anaemia prevention strategies. Methods This cross-sectional study enrolled 1500 pregnant women from Narayanganj district, Bangladesh, during their second or third trimester. Anaemia and iron status were described and their relationship with drinking water iron assessed using regression analyses. Results The prevalence of anaemia was 38% (95% confidence interval, CI: 35%, 40%), with 10% (95% CI: 9%, 12%) experiencing moderate-to-severe anaemia. Iron deficiency affected 48% (95% CI: 45%, 50%) of participants. Although drinking water iron concentrations were generally low (median: 0 mg/L; interquartile range: 0–1), high concentrations (≥ 2 mg/L) were associated with increased ferritin levels but did not significantly impact iron deficiency (95% CI: 0·73, 1·02) or anaemia (95% CI: 0·79, 1·17) prevalence. Iron deficient women had a 1·86 (95% CI: 1·61, 2·15) adjusted prevalence ratio for anaemia and a 4·22 (95% CI: 2·89, 6·17) adjusted prevalence ratio for moderate-to-severe anaemia, compared to iron replete women. Conclusions Anaemia and iron deficiency are highly prevalent among pregnant women in Narayanganj. These findings challenge the assumption of low iron deficiency prevalence throughout Bangladesh and highlight iron deficiency in pregnancy as a potentially underrecognized public health problem, particularly in regions with low drinking water iron. Further research is needed to clarify the contribution of drinking water iron to iron deficiency and anaemia in Bangladesh. Trial registration The study is registered with the Australian and New Zealand Clinical Trials Registry (ACTRN12621000982819, registered 26/07/2021)